Modification of nanosized LiFePO4 via nickel doping and graphene coating. (23rd May 2019) - Hang, La Thi; Anh, Nguyen Thi My; Tru, Nguyen Nhi; Nguyen, Huynh Le Thanh; Phung, Le My Loan
In this study, LiFe1-x Nix PO4 and LiFe1-x Nix PO4 /graphene (LFNP/Gr) composites were synthesised via solvothermal route. The phase structure was characterised by X-ray diffraction (XRD) and energy dispersive X-ray spectroscopy (EDS). The graphene coating was confirmed by Raman spectroscopy; the particle morphology and size were defined through SEM and TEM images observation. The expected material design was given with nickel doping and graphene coating process. Particle size of the synthesised LiFe1-x Nix PO4 /graphene was proved to be reduced from 400 nm to approx. 40 nm comparing to the pristine LFP. Meanwhile, the nickel doping and graphene coating gave a significant increase of conductivity for LiFe1-x Nix PO4 and LiFe1-x Nix PO4 /graphene as 2 × 10 -3 and 1.5 × 10 -2 S/cm respectively, comparing to pristine LiFePO4 (10 -6 S/cm). The discharge capacity of LiFe1-x Nix PO4 /graphene was in range of 120-145 mAh/g and remained nearly 80% efficient after 20th cycles.